Pengaruh Cara Pengeringan Simplisia Daun Senggani (Melastoma malabathricum L.) Terhadap Aktivitas Antioksidan Menggunakan Metode DPPH (2,2-difenil-1-pikrilhidrazil) - Sri Luliana; Nera Umilia Purwanti; Kris Natalia Manihuruk (Universitas Indonesia, 2016)
Drying is the most important step to keep the compound stability in simplicia. The aimed of this study was to know the effect of drying methods on antioxidant activity in Melastoma malabathricum L. The drying methods were tested on oven-drying at 40°C, direct sunlight, indirect sunlight, air-drying at ± 25°C and fresh samples as control. The result revealed that the drying methods of simplicia were significant differences for antioxidant activity in Melastoma malabathricum L. (p<0,05). Drying method that has the highest antioxidant activity was by air-drying at ± 25°C is 54.60%.